Evaluation of bond strength of glass and resin-ceramics with laser phototherapy: A systematic review and meta-analysis of in vitro studies - Nascimento, Victor Alves [UNESP]; Bento, Victor Augusto Alves [UNESP]; Cruz, Kevin Henrique [UNESP]; Rosa, Cleber Davi Del Rei Daltro [UNESP]; Pesqueira, Aldiéris Alves [UNESP]; Pellizzer, Eduardo Piza [UNESP] (Elsevier, 2023)
Statement of problem: Laser phototherapy has been studied as a surface treatment capable of increasing the adhesion of cement to the ceramic surface. However, the bond strength of glass and resin-ceramics after laser phototherapy is unclear. Purpose: The objective of this systematic review and meta-analysis was to compare the bond strength of glass and resin-ceramics using laser therapy and conventional hydrofluoric acid etching. Material and methods: This systematic review and meta-analysis followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and was registered in the Open Science Framework (OSF) for in vitro studies. A population, intervention, control, and outcome (PICO) question was formulated: “Does phototherapy promote better bond strength in glass and resin-ceramics than conventional hydrofluoric acid etching?” A literature search was performed in PubMed/MEDLINE, Embase, Web of Science, Scopus, Cochrane Library, and ProQuest databases up to January 2023. The Joanna Briggs Institute critical assessment guidelines for quasi-experimental studies were used for quality assessment. The meta-analysis was based on the inverse variance (IV) method (α=.05). Results: A total of 6 in vitro studies published between 2007 and 2019 with a total number of 348 specimens were included for qualitative analysis; 1 study had a positive effect. Five of the studies were included in the meta-analysis, which indicated a significant decrease for feldspathic ceramics that received laser phototherapy and lithium disilicate (P=.002; MD: −2.15; 95% CI: −3.53 to −0.77; I2=89%, P<.01) and (P<.01; MD: −2.13; 95% CI: −2.99 to −1.27; I2=82%, P<.01), respectively. Conclusions: Laser irradiation as surface etching of glass ceramics does not produce a bond strength equal to that of conventional hydrofluoric acid etching.